The Influences of the Board of Commissioners, Board of Directors, Audit Committee, Managerial Ownership, and Company Size toWDP Opinion - Munifah, Siti; Suryandari, Dhini (UNIVERSITAS NEGERI SEMARANG, 2019)
The research is aimed to examine the effect of board of commissioners, board of directors, audit committee, managerial ownership, and firm size on receiving qualified audit opinion. Population of this research are 198 companies in infrastructure, utility, and transportation sector which are listed on Indonesian Stock Exchange in 2013-2016. Sample in this research was selected by using purposive sampling method and yielded 88 unit of analysis. This research use regression logistic analysis. The result shows that board of commissioners negatively influence the receiving qualified audit opinion. The existence of board of commissioners as supervisory board give positive impact to better accounting practise, so that decrease the probability of receiving qualified audit opinion. The result also shows that firm size negatively influence the receiving qualified audit opinion. Firm size encourages companies to produce a good financial statement so that decrease the probability of receiving qualified audit opinion. Variables board of directors, committee audit, and managerial ownership were not influence the receiving qualified audit opinion. The conclusion of this research is corporate governance structure cannot decrease the probability of receiving qualified audit opinion directly.